The role of bank advisors in mergers and acquisitions - Linda Allen; Julapa Jagtiani; Stavros Peristiani; Anthony Saunders (Federal Reserve Bank of New York, 2002)
This paper looks at the role of both commercial and investment banks in providing merger advisory services. In this area, unlike some areas of investment banking, commercial banks have always been allowed to compete directly with investment banks. In their dual role as lenders and advisors to firms that are the target or the acquirer in a merger, banks can be viewed as serving a certification function. However, banks acting as both lenders and advisors face a potential conflict of interest that may mitigate or offset any certification effect. Overall, we find evidence supporting the certification effect for target firms. In contrast, conflicts of interest appear to dominate the certification effect when banks are advisors to acquirers. In particular, the target earns higher abnormal returns when the target's own bank certifies the (more informationally opaque) target's value to the acquirer. In contrast, we do not find a certification role for acquirers. There are two possible reasons for these different outcomes. First, it is the target firm, not the acquirer, that must be priced in a merger. Second, acquirers predominantly use commercial bank advisors to obtain access to bank loans that may be used to finance the merger. Thus, we find that acquirers tend to choose their own banks (those with prior lending relationships to the acquirer) as advisors in mergers. However, this choice weakens any certification effect and creates a potential conflict of interest because the acquirer's advisor negotiates the terms of both the merger transaction and future loan commitments. Moreover, the advising bank's recommendations may be distorted by considerations related to credit exposure incurred in both past and future lending activity. The market prices these conflicts of interest; we find significantly negative abnormal returns for bank advisors when they advise their own loan customers in acquiring other firms.
Keywords: G21; 330; Relationship banking; investment bank advisors; commercial bank advisors; certification effect; conflict of interest effect; mergers; acquisitions; Fusion; Übernahme; Bank; Investmentbank; Anlageberatung; USA